2014
DOI: 10.3390/antibiotics3020109
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy of a Single Two Gram Dose of Azithromycin Extended Release for Male Patients with Urethritis

Abstract: To clarify the clinical efficacy of a single oral 2 g dose of azithromycin extended-release for heterosexual male patients with urethritis, and the current antimicrobial sensitivity of Neisseria gonorrhoeae to azithromycin, a prospective clinical trial was conducted from 2011–2013. In patients with gonococcal urethritis, the eradication rate was 90.9% (30 of 33). The susceptibility rates of isolated Neisseria gonorrhoeae strains to ceftriaxone, spectinomycin, cefixime and azithromycin were 100%, 100%, 95.3% (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 27 publications
0
16
0
2
Order By: Relevance
“…The overall AE rate, speci cally the GI AE rate, was much higher than most studies that have utilized 2 grams of AZ. Studies to treat male urethritis with a single dose of 2 gm showed GI AE rates around 35% [25,26]. The Zithromax ® drug label cites overall GI rates of around 46% with use of 2 gm.…”
Section: Discussionmentioning
confidence: 99%
“…The overall AE rate, speci cally the GI AE rate, was much higher than most studies that have utilized 2 grams of AZ. Studies to treat male urethritis with a single dose of 2 gm showed GI AE rates around 35% [25,26]. The Zithromax ® drug label cites overall GI rates of around 46% with use of 2 gm.…”
Section: Discussionmentioning
confidence: 99%
“…In cases in which a single 2-g dose of AZM-SR was used, gastrointestinal symptoms were more likely to occur in Japanese patients (approximately 30%) (13, 14). However, the symptoms were mostly temporary and were resolved within a day when the patients took AZM-SR (13,14). Taken together, when a single 2-g dose of AZM-SR is administered with or without other antibiotics to Japanese patients, the patients should be carefully monitored for gastrointestinal adverse events, particularly within 1 day after AZM-SR administration.…”
Section: Discussionmentioning
confidence: 99%
“…Although a single 2-g dose of an immediate-release formulation of AZM (conventional AZM) remains effective against uncomplicated gonorrhea (12), this monotherapy could cause an unacceptable rate of adverse events, particularly gastrointestinal upset. Recently, a single 2-g dose of a microsphere-based extended-release formulation of AZM (AZM-SR) was developed and was found to be effective against N. gonorrhoeae (13)(14)(15), and the frequency of adverse events also decreased compared with that achieved with a single 2-g dose of conventional AZM (12,(15)(16)(17)(18). Therefore, a single 2-g dose of AZM-SR is considered useful for the treatment of gonorrhea.…”
mentioning
confidence: 99%
“…21,22 Dean et al reported poor tolerability in participants receiving a 1 g single dose of azithromycin followed by 500 mg daily for 4 days in a treatment study on Pelvic Inflammatory Disease (PID); 61% of the cohort experienced diarrhoea, of whom nearly 75% described this as being moderate or severe. 23 Interestingly, studies for the treatment of syphilis using a 2 g single dose of azithromycin report lower rates of nausea and diarrhoea (9-13%) 24,25 for reasons that are unclear, but may reflect the subjective nature of reporting side-effects and lack of standardisation.…”
Section: Azithromycinmentioning
confidence: 99%